INTERPRETING A POEM OF BEN JONSON, “SONG: TO CELIA” - Nanik Mariana Effendie (English Department of Faculty of Tarbiyah and Teacher Training, 2012)
ABSTRACTDiscourse analysis is analysis of language in use (Brown and Yule, 1983). How the language-users interpret what other language-users intend to convey and how they make sense of what they read in texts, understand what speakers mean despite what they say, recognize connected as opposed to jumbled or incoherent discourse, and successfully take part in that complex activity called conversation. A poem can be interpreted through discourse analysis approach (Brown and Yule, 1983). Using this approach, the meaning of a poem can be revealed exactly the same as or very close to what the poet want to say or send the message. This article tries to interpret “Song: To Celia”, one of Ben Jonson’s poems through knowledge of the world or schema, context and coherence. Knowledge of the world or Schema plays key roles in many cognitive processes. They help us pay attention, comprehend, interpret, remember, make inferences, set expectations, reason, solve problems, understand language structures, read, write, explain what we know, and have a sense of humor. To interpret this poem, knowledge about love is important, and also the schemata about who the speakers and the listeners are. The speaker in